2016
DOI: 10.1007/s10514-016-9553-5
|View full text |Cite
|
Sign up to set email alerts
|

Human sit-to-stand transfer modeling towards intuitive and biologically-inspired robot assistance

Abstract: Sit-to-stand (STS) transfers are a common human task which involves complex sensorimotor processes to control the highly nonlinear musculoskeletal system. In this paper, typical unassisted and assisted human STS transfers are formulated as optimal feedback control problem that finds a compromise between task end-point accuracy, human balance, energy consumption, smoothness of motion and control and takes further human biomechanical control constraints into account. Differential dynamic programming is employed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 40 publications
0
37
0
Order By: Relevance
“…One key concern, and identified area for robotic assistance, are transfers-for example, in and out of a bed or a wheelchair, or from sitting to standing-because of the risk of falls and injury. In this Special Issue, the work of Geravand et al (2016) formulates sit-to-stand transfers as an optimal feedback control problem, which optimizes over factors like accuracy, human balance, energy, motion smoothness and human biomechanical constraints. Their approach is evaluated with a robotic assistant and aged persons largely unable to perform sit-to-stand transfers unassisted.…”
Section: Assistive Robots For Manipulation and Mobilitymentioning
confidence: 99%
“…One key concern, and identified area for robotic assistance, are transfers-for example, in and out of a bed or a wheelchair, or from sitting to standing-because of the risk of falls and injury. In this Special Issue, the work of Geravand et al (2016) formulates sit-to-stand transfers as an optimal feedback control problem, which optimizes over factors like accuracy, human balance, energy, motion smoothness and human biomechanical constraints. Their approach is evaluated with a robotic assistant and aged persons largely unable to perform sit-to-stand transfers unassisted.…”
Section: Assistive Robots For Manipulation and Mobilitymentioning
confidence: 99%
“…The sample size of included studies averaged 7.7 ± 4.5 subjects (range, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The mean age of subjects ranged from 25 [37] to 89 years [38], with age information lacking in four studies [17,[25][26][27].…”
Section: Study Samplementioning
confidence: 99%
“…In our recent systematic review on the methodology of studies evaluating RRs by the user perspective, the identified studies showed large heterogeneity in study population, design of studies/test scenarios, and assessment methods. No generic methodology to evaluate RRs from the user perspective could be identified [19]. We also found major methodological shortcomings related to insufficient sample sizes, lack of appropriate standardized and validated assessment methods, and lack of statistical analyses of study results.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Gervand et al [6] formulated unassisted and assisted STS transfers as a control problem and found a balance among the end-point accuracy, human balance, energy consumption, and smoothness of motion. Chuy et al [7] presented two approaches to assisting with the STS movement by using a robotic walking support system and showed that this system can track the desired support force.…”
Section: Introductionmentioning
confidence: 99%